Single-Dose 13-Valent Conjugate Pneumococcal Vaccine in People Living With HIV – Immunological Response and Protection - Romaru, Juliette; Bahuaud, Mathilde; Lejeune, Gauthier; Hentzien, Maxime; Berger, Jean-Luc; Robbins, Ailsa; Lebrun, Delphine; N’Guyen, Yohan; Bani-Sadr, Firouzé; Batteux, Frédéric; Servettaz, Amélie (Frontiers in Immunology, 2021)
Background Patients living with HIV (PLHIV) are prone to invasive pneumococcal disease. 13-valent conjugated pneumococcal vaccine (PCV13) is currently recommended for all PLHIV, followed in most guidelines by a 23-valent polysaccharidic pneumococcal vaccine. Data are scarce concerning immunological efficacy of PCV13 among PLHIV. Objective: To assess one-month immunological response, and 1-, 6- and 12-month immunological protection, both in ELISA and opsonophagocytic assay (OPA), after a single dose of PCV13 in PLHIV with a CD4 cell count above 200/mm3. Methods: PLHIV with CD4 cell count >200/mm3 were included. Specific IgG serum concentrations for 8 serotypes by ELISA and 7 serotypes by OPA were measured at baseline, 1-, 6- and 12 months after PCV13 vaccination. Global response was defined as a two-fold increase from baseline of specific IgG antibody levels (μg/ml) assayed by ELISA or as a four-fold increase in OPA titer from baseline, for at least 5 serotypes targeted by PCV13. Global protection was defined as an IgG-concentration ≥1 µg/mL by ELISA or as an opsonization titer ≥LLOQ by OPA for at least five tested serotypes targeted by PCV13. Factors associated with global response and global protection were assessed using logistic regression. Results: Among 38 PLHIV included, 57.9% and 63.2% were global responders, 92.1 and 78.9% were 1-month globally protected and 64.7% and 55.9% were still 12-months globally protected, by ELISA and OPA respectively. A CD4/CD8 ratio >0.8 was significantly associated with a better global response by OPA (OR=6.11, p=0.02) and a CD4 nadir <200 was significantly associated to a poorer risk of global response by ELISA (OR=0.22, p=0.04). A CD4 cell count nadir <200 and patients aged over 50 were associated with poorer global protection by OPA at M1 (OR=0.18, p=0.04) and M12 (OR= 0.15, p=0.02), respectively. Conclusion: Vaccination with PCV13 in these patients allowed immunological response and protection at one month. At one year, more than half of patients were still immunologically protected.